Vagus Nerve Stimulation Induced Motor Map Plasticity Does Not Require Cortical Dopamine - Brougher, Jackson; Sanchez, Camilo A.; Aziz, Umaymah S.; Gove, Kiree F.; Thorn, Catherine A. (Frontiers in Neuroscience, 2021)
Background: Vagus nerve stimulation (VNS) paired with motor rehabilitation is an emerging therapeutic strategy to enhance functional recovery after neural injuries such as stroke. Training-paired VNS drives significant neuroplasticity within the motor cortex (M1), which is thought to underlie the therapeutic effects of VNS. Though the mechanisms are not fully understood, VNS-induced cortical plasticity is known to depend on intact signaling from multiple neuromodulatory nuclei that innervate M1. Cortical dopamine (DA) plays a key role in mediating M1 synaptic plasticity and is critical for motor skill acquisition, but whether cortical DA contributes to VNS efficacy has not been tested. Objective: To determine the impact of cortical DA depletion on VNS-induced cortical plasticity. Methods: Rats were trained on a skilled reaching lever press task prior to implantation of VNS electrodes and 6-hydroxydopamine (6-OHDA) mediated DA depletion in M1. Rats then underwent training-paired VNS treatment, followed by cortical motor mapping and lesion validation. Results: In both intact and DA-depleted rats, VNS significantly increased the motor map representation of task-relevant proximal forelimb musculature and reduced task-irrelevant distal forelimb representations. VNS also significantly increased tyrosine hyrdoxylase (TH+) fiber density in intact M1, but this effect was not observed in lesioned hemispheres. Conclusions: Our results reveal that though VNS likely upregulates catecholaminergic signaling in intact motor cortices, DA itself is not required for VNS-induced plasticity to occur. As DA is known to critically support M1 plasticity during skill acquisition, our findings suggest that VNS may engage a unique set of neuromodulatory signaling pathways to promote neocortical plasticity.